Supporting early document navigation with semantic zooming - Owen, Tom H.; Buchanan, George R.; Eslambochilar, Parisa; Loizides, Fernando (My University, 2010)
Traditional digital document navigation found in Acrobat and HTML document readers performs poorly when compared to paper documents for this task. We investigate and compare two methods for improving navigation when a reader first views a digital document. One technique modifies the traditional scrolling method, combining it with Speed-Dependent Automatic Zooming (SDAZ). We also examine the effect of adding "semantic" rendering, where the document display is altered depending on scroll speed. We demonstrate that the combination of these methods reduces user effort without impacting on user behaviour. This confirms both the utility of our navigation, and the minimal use information seekers use of much of the content of digital documents
Keywords: Information science; Information technology; Digital libraries; Documentation